Effect of Different Diluent and Binder Types on the Preparation of Bisoprolol Fumarate as Tablet Dosage Form - Heba A. Fatohy; Alaa A. Abdul-Rasool (College of Pharmacy University of Baghdad, 2017)
Hypertension is one of the main causes of heart disease; beta- blockers play a crucial role in the management of patients with essential hypertension. Bisoprolol is one of the widely used drugs for the treatment of hypertension. Bisoprolol tablets were prepared by two methods (direct and wet) using different proportion and types of diluents, different binder types and forms, then evaluated for, weight variation, hardness, friability, disintegration time and dissolution rate. The results were compared with a reference Bisoprolol tablet. Both methods of preparation wet and direct compression method gave good results, which are consistent with the requirements of British Pharmacopeia and United States Pharmacopeia. It was found that the type of diluent (mannitol and lactose), binder type (polyvinyl pyrrolidone and acacia) and the presence of starch as a disintegrant affect the hardness, disintegration and the dissolution rate of the tablet. While liquid binder (polyvinyl pyrrolidone solution) gave longer disintegration time (12 min) with higher hardness compared with the powdered binder (polyvinyl pyrrolidone powder) that gave (5 min). The results indicate that formula F1 which consists of [Mannitol (65mg)/ Avicel 102 (26 mg), starch and magnesium stearate] showed the best results as it has lower disintegration time (2.7 min), faster dissolution rate (100% release within 20 min) and prepared by a low cost method (direct method). Key words: Bisoprolol, diluent, binder, direct compression, wet granulation.